2009
DOI: 10.3748/wjg.15.3757
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated shRNA interference targeting STAT3 inhibits human pancreatic cancer cell invasion

Abstract: AIM:To investigate RNA interference targeting signal transducer and activator of transcription-3 (STAT3) on invasion of human pancreatic cancer cells. METHODS:We constructed three plasmids of RNA interference targeting the STAT3 gene. After LV (lentivirus)-STAT3siRNA (STAT3 small interfering RNA) the vector was transfected into the human pancreatic cell line, SW1990 and cell proliferation was measured by the MTT assay. Flow cytometry was used to assess cell cycle. Vascular endothelial growth factor (VEGF) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…In pancreatic cancer, down-regulation of STAT3 expression suppressed the growth and invasiveness of cancer cells, both in vitro and in vivo [27, 38]. In the present study, we observed that OSU-A9 significantly inhibited cell migration and invasiveness of BxPC-3 and PANC-1 cells (Figure 5).…”
Section: Discussionsupporting
confidence: 58%
“…In pancreatic cancer, down-regulation of STAT3 expression suppressed the growth and invasiveness of cancer cells, both in vitro and in vivo [27, 38]. In the present study, we observed that OSU-A9 significantly inhibited cell migration and invasiveness of BxPC-3 and PANC-1 cells (Figure 5).…”
Section: Discussionsupporting
confidence: 58%
“…In pancreatic cancer, activation of STAT3 promoted tumor cell growth and invasion, which led to poor patient survival [22]. Furthermore, STAT3 knockdown inhibited the cell growth and invasiveness in pancreatic cancer both in vitro and in vivo , and markedly decreased VEGF and MMP-2 expressions [23], [24]. Therefore, the dual luciferase assay was applied to identify whether STAT3 was directly targeted by miR-130b.…”
Section: Introductionmentioning
confidence: 99%
“…Signal transducer and activator of transcription-3 protein (STAT3) is the most important member of the family of STAT, which has been reported to promote tumor proliferation, survival and angiogenesis by upregulating the expression of anti-apoptotic proteins (survivin, Bcl-xL and Mcl-1), cell cycle regulators (cyclin D1and c-Myc) and vascular endothelial growth factor (VEGF) [12][13][14][15]. STAT3 has been found to be highly up-regulated in many human cancers, such as breast cancer, renal cell carcinoma, bladder cancer, urothelial carcinoma, prostate cancer, and lung cancer [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%